MICROFINANCE BANKS SERVICES AND SALES GROWTH OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) IN SOUTH-WEST, NIGERIA (Journal of the Management Sciences, 2024)
This study examined how microfinance banks services affect sales growth of micro, small, and medium-sized enterprises' (MSMEs) in South-West, Nigeria. A proportionate stratified sampling strategy was employed to implement a descriptive research design. The study's sample size of 400 was determined using the Taro Yamane formula. The data was analysed using Statistical Packages for Social Sciences (SPSS) version 26, which was utilized to test the hypothesis using both descriptive and inferential statistics. Findings revealed that all microfinance bank services significantly boost MSMEs' sales growth in South-West, Nigeria. The study came to the conclusion that MSMEs in South-West Nigeria's product development is positively and significantly impacted by the services provided by microfinance banks. The study recommends that microfinance banks should improve on the number of loans/credits granted to MSMEs in order to eventually translate to economic growth.
Keywords: Micro-savings, micro-credits, micro-insurance, sales growth, micro, small, and medium enterprises (MSMEs)